GLP-1–Based Therapies Have No Microvascular Effects in Type 2 Diabetes Mellitus: An Acute and 12-Week Randomized, Double-Blind, Placebo-Controlled Trial. Issue 10 (October 2016) - Smits, Mark M.; Tonneijck, Lennart; Muskiet, Marcel H.A.; Hoekstra, Trynke; Kramer, Mark H.H.; Diamant, Michaela; Serné, Erik H.; van Raalte, Daniël H.
Abstract : Objective—: To assess the effects of glucagon-like peptide (GLP)-1–based therapies (ie, GLP-1 receptor agonists and dipeptidyl peptidase-4 inhibitors) on microvascular function in patients with type 2 diabetes mellitus. Approach and Results—: We studied 57 patients with type 2 diabetes mellitus (mean±SD age: 62.8±6.9 years; body mass index: 31.8±4.1 kg/m 2 ; HbA1c [glycated hemoglobin] 7.3±0.6%) in an acute and 12-week randomized, placebo-controlled, double-blind trial conducted at the Diabetes Center of the VU University Medical Center. In the acute study, the GLP-1 receptor agonist exenatide (therapeutic concentrations) or placebo (saline 0.9%) was administered intravenously. During the 12-week study, patients received the GLP-1 receptor agonist liraglutide (1.8 mg daily), the dipeptidyl peptidase-4 inhibitor sitagliptin (100 mg daily), or matching placebos. Capillary perfusion was assessed by nailfold skin capillary videomicroscopy and vasomotion by laser Doppler fluxmetry, in the fasting state and after a high-fat mixed meal. In neither study, treatment affected fasting or postprandial capillary perfusion compared with placebo ( P >0.05). In the fasting state, acute exenatide infusion increased neurogenic vasomotion domain power, while reducing myogenic domain power (both P <0.05). After the meal, exenatide increased endothelial domain power ( P <0.05). In the 12-week study, no effects on vasomotion were observed. Conclusions—: Despite modest changes in vasomotion, suggestive of sympathetic nervous system activation and improved endothelial function, acute exenatide infusion does not affect skin capillary perfusion in type 2 diabetes mellitus. Twelve-week treatment with liraglutide or sitagliptin has no effect on capillary perfusion or vasomotion in these patients. Our data suggest that the effects of GLP-1–based therapies on glucose are not mediated through microvascular responses. Abstract : Supplemental Digital Content is available in the text.